Specific heat, magnetic susceptibility and electrical resistivity measurements on LaNiO3 - Sanchez, R.D.; Causa, M.T.; Sereni, J.G.; Vallet-Regi, M.; Sayaguez, M.J.; Gonzalez-Calbet, J.M.; Sereni, Julián (Elsevier, 1993)
Fil: Sanchez, R.D. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina